Road Condition Estimation with Data Mining Methods using Vehicle Based Sensors - Masino, Johannes (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2021)
The work provides novel methods to process inertial sensor and acoustic sensor data for road condition estimation and monitoring with application in vehicles, which serve as sensor platforms. Furthermore, methods are introduced to combine the results from various vehicles for a more reliable estimation.